An Ideal Concept of Ad Hoc General Election Supervisors to Handle The Code of Ethics - Idhar, Idhar; Hasanah, Siti; Jiwantara, Firzhal Arzhi (JILPR Journal Indonesia Law and Policy Review, 2024)
It is crucial to establish a code of ethics for ad hoc General Election observers in order to guarantee the integrity, fairness, and transparency of the democratic process. The objective of this research is to identify and examine the optimal approach for addressing infractions of the Code of Ethics for Ad Hoc General Voter Supervisors. The research employed normative legal research methodology, specifically utilizing a statutory and conceptual approach. An effective approach to addressing violations of the code of ethics for ad hoc general voter supervisors is to withdraw the authority of The General Election Supervisory Agency in handling such violations. This is in accordance with Article 10 of DKPP Regulation Number 3 of 2017, which has been recently amended through Election Organizer Ethics Council (DKPP) Regulation Number 1 of 2021. The amendment establishes a Regional Audit Team at the Regency/City level to conduct inspections and address code of ethics violations committed by ad hoc general voter supervisors.